Flâneurs - Street Rambles - Lancit, Matthew (Journal of Anthropological Films, 2024)
Between film projects and following the birth of his daughter, a Canadian in Paris (Matthew Lancit) must confront his slacker lifestyle and decide if there is something in it worth passing on to the next generation, or if he is better off getting a job. In search of the remaining traces of flâneurs (19th Century wanderers of Paris), he takes his daughter on a series of poetic strolls in which he assumes the role of a contemporary flâneur and crosses the path of people who help reveal the relevance of such a figure today. In the movement back and forth between the filmed streets of Paris and scenes from the domestic life of a young father, a dialectic emerges between a baby experiencing and making sense of the world and these wandering men trying to do the same.